P and Q Models of Material Inventory Control Systems on Snack Production in Traditional Snack Company Malang - Pulungan, M. Hindun; Sukardi, Sukardi; Rofida, Siti (Fakultas Teknologi Pertanian Universitas Brawijaya, 2001)
In the company, materials inventory control system show the supply of materials repeatedly occurs but the demand of materials dependently on the rate of productions. Refer on this condition, statistic method used for materials inventory control, i.e. P and Q model. They are determines the quantity the time of ordering materials to minimize total inventory cost.The Q model parameter comprises of ordering materials quantity, ordering time, and buying price. The changes of Q model parameter to 90% affect on optimum ordering quantity but it is not change the model. On P model the changes of quantity of ordering materials to 90% influence to maximum inventory but it is not change the model. The changes on ordering time and buying price didn’t affect to rate of maximum inventory nor to change the model.On Q and P model application, the broken materials rate only depend on the weight of bowl and the shrink of materials weight, so it is important to investigate broken chemically pattern of materials when storage time. In addition, application of both models based on constant rate production capacity, so it is important too, to investigate materials inventory model if the company widened or production capacity increased.Keywords: P and Q model, material inventory control system, snack production